Rupture of renal artery aneurysm during cesarean section: a case report: Ruture of renal artery aneurysm r cesarean seection - Aljanabi, Rawaa Dawood; Al-Diwan, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2020)
Introduction:Renal artery aneurysm (RAA) occurs to focal dilatation of artery secondary to weakness of the arterial intima and media. RAA is a rare clinical entity with an incidence of 0.01 – 1%.1Rupture RAA during pregnancy is extremely rare event. The obstetric and urologic literatures are deficient in this regard. Diagnosis of rupture RAA during pregnancy is very difficult i.e. no pathognomonic presentation. When rupture occurs during pregnancy the clinical presentation is confused with those more common conditions e.g. placenta abruption or rupture uterus. Most of the cases are discovered incidentally, even it is only diagnosed after autopsy.Case presentation:A fifth cesarean section was done for 30 years oldwomen presented with placenta previa. She was gravida 6 para 5. Cesarean section was an elective one. She gave a live birth male weighing 2.4 kg.  Hysterectomy was carried out after sever bleeding during operation. Ten units of blood were given in addition to other management steps. Urologists and general surgeon were consulted. The patient was dead. Exploration was done and revealed a rupture of left renal artery aneurysm.  Discussion:It was the 5th cesarean section for women. Literature documented that previous history of cesarean sections is the primary risk factor for developing placenta previa.1 Other risk factors are gestation with male fetuses and multiparity.3 The mentioned risk factors were characters of the reported case. It was stressed that multiple cesarean sections affect adversely the health of women.2 It was the 5thcesarean section. RAA is an unusual diagnosis. Hemodynamic changes during pregnancy that is increased blood volume and cardiac output, raised intrabdominal pressure and hormonal alterations, affect the arterial wall and increased the risk of rupture RAA, more so in the 3rdtrimester.3 The reported case was gravida 6 which might enhanced the formation and rupture of RAA. It was reported that women with RAA and unusual number of women were multiparous.4Owing to the pregnancy state, RAA was missed as ​cesarean section was planned for delivery of acase of placenta previa. The final diagnosis made only after exploration. It is the same as mentioned in literature.5In this case, RAA was on the left side. Literature reported that RAA was often on the left side.4 Since 1970, published reports have not shown a left sided predominance of RAA.6There are no previous reports of diagnosis of the intact RAA during pregnancy. This report might be the first one in Iraqi literature of rupture of RAA during pregnancy. Conclusion: The possibility of a ruptured RAA should be considered in pregnant women with evidence of retroperitoneal hemorrhage. Imaging facilities should be available in theater rooms to be used immediately.  References:1- Oylele Y, Smulian JC. Placenta previa, placenta accrete and vasa previa. Obstet Gynecol 2006; 107: 927-941.2- Seidman DS, Pazi I, Nadu A, Dollberd S, Stevenson DK, Gele R et al. Are multiple cesarean sections safe? Eur J Obstet Gynecol Reported Biol 1994; 57: 7-123- Porcaro AB, Migliorini F, Pianon R, Antoniothi SZ, Furlan F, De Biase V et al. Intraparenchymal renal artery aneurysms. Case report with review and update of literature. Int Urol Nephrol 2004; 36: 409-416.4- Soliman KB, Shawky A, Abbas MM. Ammory M, Shoaban A. Rupture renal artery aneurysm during pregnancy. A clinical dilemma. BMU Urol 2006; 6: 225- Henke PK, Cardnean D, Welling III TH, Upchurch GR, Wakefield TH, Jacob L et al. Renal artery aneurysm: a 35-year clinical experience with 252 aneurysms in 168 patients. Annal of Surgery 2001; 214: 454-463.6- Yang JC, Hye RJ. Ruptured renal artery aneurysm during the pregnancy. Ann Vasc Surg 1996; 10: 370-372. 2